ARCHITECTURE OF COMPUTER NETWORKS FOR FOUR FLOOR BUILDINGS AT WIDYATAMA UNIVERSITY USING DHCP CONFIGURATION ON CISCO PACKET TRACER - Suryana, Ase; R. , Susanto; Pramudita, Resa; Fadzri, Rifqi (International Journal of Psychosocial Rehabilitation, 2020)
This paper discusses the architecture of computer networks in a four-floor building at Widyatama University. Switches are used to connect devices such as computers, printers, and laptops so that all networks are connected. Dynamic Host Configuration Protocol (DHCP) configuration is used in assigning IP addresses to devices. There is also a simulation using packet tracer, a simulation for computer networks for students in version 6.2.